BARRIERS TO LEARNING TO READ THE QUR'AN AMONG STUDENTS AND TEACHERS’ METHODS FOR OVERCOMING THEM - Irnawati; Yuliana Afifah (Academic Bright Collaboration, 2026)
This study aims to examine the process of learning to read the Qur’an, identify barriers and factors causing difficulties in reading the Qur’an among seventh-grade students in Class VII A, and analyze teachers’ efforts to overcome these barriers in learning to read the Qur’an at SMP Negeri 60 Muaro Jambi. This study employed a qualitative approach using the case study method. Data collection techniques included observation, interviews, and documentation. The research informants consisted of Islamic Religious Education teachers and seventh-grade students in Class 7A at SMP Negeri 60 Muaro Jambi. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results of the study indicate that students’ ability to read the Qur’an varies. Some students are already able to read the Qur’an fairly fluently, while others still face difficulties in recognizing the Arabic alphabet, understanding the articulation points of letters, and applying the rules of tajwid. The main obstacles identified include low learning motivation, a lack of practice reading the Qur’an at home, limited learning time, and minimal family support. Teachers used the talaqqi method, group reading, reading demonstrations, repetitive practice, and individual instruction to help students improve their Qur’an reading skills. This study indicates that Quranic reading instruction requires varied methods, sustained practice, and support from both the family and the school environment. The limitation of this study lies in its scope, which was confined to a single class and a single school; therefore, the findings cannot yet be widely generalized. This study possesses originality as it thoroughly examines the barriers to Quranic reading instruction alongside the methods teachers employ to address them within the context of junior high school students in rural areas. It is hoped that this study will serve as a reference for Islamic Religious Education teachers in enhancing the effectiveness of Quranic reading instruction.